PERANCANGAN APLIKASI PENJUALAN OBAT PADA APOTEK ONE FARMA - hasbi, hasbi; Muid, Ermius; Jamila, Nur (DINAMIS, 2020)
The purpose of this study was to conduct research on the Application of Drug Stock Management at One Farma Pharmacy so that the archiving process no longer used archive books. Therefore this study designed an application that can make it easier for employees at One Farma pharmacies to make reports. In this research process to facilitate research in obtaining accurate information, this study uses the methodology of observation, interviews and literature study so that the data obtained is in accordance with the facts. in the field. For data analysis techniques using the waterfall paradigm and the system design method used is the Data Flow Diagram to make it easier to design applications that are made. As for the programming language used in designing this application, the Visual Basic 6.0 programming language and the MYSQL database are used in creating the database needed in the application to be created. The results of this study indicate that with the application of the Drug Stock management application at One Farma Pharmacy, pharmacy employees can easily create reports, stock drugs, purchase and sale of drugs and facilitate data archiving without having to be archived using conventional methods or archiving books with such problems. by One Farma, pharmacy employees can be equipped with a system that has been created.